The Authority and Ownership of Muddy Land (Aanslibbing) at North Coastal Area of Java Sea - Muhibbin, Moh (Institute of Research and Community Service, University of Brawijaya, 2015)
The mud islands referred to as muddy land are a new natural resource that in economical terms is potential for farming and brackish-water business resulting in the authority and ownership of the land by the local society. On the one hand, the written state law suggests that muddy land is state propety dominated by government. In fact, history shows that local society has authority over it for generation according to the prevailing customs.The authority of muddy land (aanslibbing) in Gresik sub-provinve and Pasuruan requaire law certainty warranty, in other words, the extension of the Indonesian Agrarian Law is still pluralistic. For the society of Gresik and Pasuruan,it could be a social sensitivity if it is not handled wisely by considering the prinsiple of certainity and usefullness.Keywords: muddy land (aanslibbing), authority and ownership